Identification of Landslide-Prone Areas Using the Horizontal to Vertical Spectral Ratio (HVSR) Method and the GIS Approach in Semakai District, Tanggamus Regency, Lampung Province - Denta Winardi Setiawan; Nandi Haerudin; Bagus Sapto; Muhammad Sarkowi; Sandri Erfani (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
Landslides are one of the natural disasters that frequently occur in Indonesia and can result in loss of life, property, and environmental damage. Semaka Subdistrict, Tanggamus Regency, Lampung Province, is located in a landslide-prone area. The aim of this research is to analyze the geological characteristics and soil layer dynamics for landslide mitigation in the Semaka area. This study uses a scoring method based on three parameters: slope inclination, sediment thickness, and peak ground acceleration (PGA), to determine site class and create a landslide-prone zone map in the Semaka region. Microtremor data is analyzed using the Horizontal to Vertical Spectrum Ratio (HVSR) method. The obtained data represents ground vibrations as a function of time, with a dominant frequency range in the Semaka area between 2.18 and 13.48 Hz and sediment thickness ranging from 10 to 80 meters. The maximum PGA values range from 100 to 600 gal. The seismic sources used in the PGA map are from the subduction zone and Semangko Fault. Based on the slope values, geological factors such as sediment thickness, and PGA values, the villages of Sedayu and Sukaraja are identified as the areas most susceptible to landslides. The findings of this research are expected to enhance landslide control measures in the Semaka region.